The Best Constant of Norm Equivalence in Orlicz Space - YANG Yabo; CUI Yunan (Journal of Harbin University of Science and Technology)
The Orlicz norm is equivalent to the Luxemburg norm. In 2011 , BANG H H, HOANG N V, HUY V N have obtained the best equivalent constant between the Orlicz norm and the Luxemburg norm in Orlicz space which generated by N-functions. The best equivalent constant between the Orlicz norm and the Luxemburg norm in Orlicz space which generated by general Orlicz functions is given.